A prospective randomized comparison of spinal versus local anesthesia with propofol infusion for knee arthroscopy - Dunn, Warren R; Cordasco, Frank A; Flynn, Erin; Jules, Kethy; Gordon, Michael; Liguori, Gregory (Arthroscopy, 2006)
Knee arthroscopy is the most common orthopaedic procedure performed in the United States, and there are few randomized studies comparing local anesthesia, in conjunction with propofol, with regional anesthesia for knee arthroscopy. The purpose of the study was to test the hypothesis that patients receiving local anesthesia combined with propofol infusion (LAP) will recover from anesthesia faster and experience less postoperative headache and back pain compared with spinal anesthesia (SA). Randomized trial. A randomized trial was used to compare SA and LAP in adults undergoing knee arthroscopy. A simple randomization scheme in sealed envelopes was used. An independent observer collected data the day of surgery and contacted patients by telephone on the first postoperative day to inquire about back pain or headaches, and to have them rate their anesthesia (excellent, good, fair, or poor). Eighteen patients (average age, 53 years) received LAP and 14 received SA. Baseline assessment of the 2 groups was similar. The mean time spent in the postoperative anesthesia care unit (PACU) was 2.8 hours for the LAP group and 4.0 hours for the SA group (P < .0001). Spinal anesthesia was associated with back pain in 5 of 14 patients in the SA group compared with none in the LAP group (P = .004). There were no statistically significant differences between the 2 groups with respect to headache (P = .5) or overall patient satisfaction (P = .3). The amount of time required to administer anesthesia was similar between the 2 groups (P = .2). The number of patients requiring additional sedation intraoperatively was higher in the LAP group compared with the SA group, 9 of 18 and 1 of 14, respectively (P = .02). Although subjects receiving LAP were more likely to require additional sedation intraoperatively compared with the SA group, LAP was associated with significantly less time to home readiness as measured by time in the PACU. Level I.